Analisis Kinerja Keuangan PT United United Tractors Tbk - Pratama, Edwin Septi Andika; Arafat, Yasir; Salmah, Ninin Non Ayu (Universitas PGRI Palembang, 2025)
ABSTRACT This research aims to determine the level of financial health of PT. United Tractors Tbk 2020 - 2022. By analyzing financial ratios in the form of liquidity (current ratio, Quick Ratio). Solvency Ratio (Debt To Total Assets, Debt To Equity Ratio), Profitability Ratio (Net Profit Margin, Return On Investment, Return On Equity), and Activity Ratio. This research uses qualitative methods, the data collection used is documentation. The results of data analysis show that: 1) the liquidity ratio in 2020-2022 means it can be concluded that Pt United Tractors Tbk experienced a decline, in 2020-2022 this company experienced a decline but it is still said to be quite good because it is still above industry standards. 2) The results of the solvency ratio in 2020-2022 for this company experienced decreases and increases but are still said to be not good because they are above industry standards. 3) Based on the Net Profit Margin calculations in 2020-2021, Pt United Tractors Tbk is still said to be not good because it is still below industry standards. In 2022, it can be said that this company will be quite good at generating profits because it is above industry standards. 4) Based on the calculation of Total Assets Turn Over which is 2 times or 200%, from 2020-2022 this company is said to be bad because it is still below industry standards, meaning this company has not been able to maximize the assets it has. Keywords: Financial Ferformance Financial Ratios. ABSTRAK Penelitian ini bertujuan untuk mengetahui tingkat kesehatan keuangan PT. United Tractors Tbk tahun 2020 - 2022. Dengan menganlisis rasio keuangan berupa likuiditas (current ratio, Quick Ratio ). Rasio Solvabilitas ( Debt To Total Assets, Debt To Equity Ratio ), Ratio Profitabilitas ( Net Profit Margin, Return On Investment, Return On Equity ), dan Rasio Aktivitas. Penelitian ini menggunakan metode kualitatif, pengumpulan data yang digunakan adalah dokumentasi. Hasil analisis data menunjukkan bahwa: 1) rasio likuiditas pada tahun 2020-2022 maka dapat disimpulkan bahwa Pt United Tractors Tbk mengalami penurunan, pada tahun 2020-2022 perusahaan ini mengalami penurunan tetapi masih di katakana cukup baik karena masih di atas standar industri. 2) Hasil rasio solvabilitas pada tahun 2020-2022 perusahaan ini mengalami penurunan dan penaikan tetapi masih di katakan kurang baik karena berada di atas standar industri. 3) Berdasarkan dari perhitungan Net Profit Margin pada tahun 2020-2021 Pt United Tractors Tbk masih di katakan kurang baik karena masih berada di bawah standar industri. Pada tahun 2022 dapat di katakana perusahaan ini cukup baik dalam menghasilkan keuntungan karena berada di atas standar industri. 4) Berdasarkan dari perhitungan Total Assets Turn Over adalah 2 kali atau 200% maka dari tahun 2020-2022 perusahaan ini dikatakan buruk karena masih di bawah standar industri, artinya perusahan ini belum mampu dalam memaksimalkan asset yang dimilikinya. Kata kunci: Kinerja keuangan, Rasio Keuangan.